RECTIFICATION THROUGH RECONFIGURATION OF ABSOLUTE FORM BOUNDARIES - Rheznindya Putra R., Mahesa
Social distancing caused by pandemic isolation which dirupted the continuity of relations became a turning point as well as a significant urge in readdressing dyadic relations as a whole. This particular experience rendered a new comprehension, which brought out an oppositional stance against various restricted yet restrictive viewpoints that accentuated relationships’ absoluteness. Thus, the work, Dyad, was aspired to liberate dyadic relations’ mechanism from the aforementioned restraining boundaries and to reconvey it as an essential experience. Form became the eminent quality in this work, considering how in the context of artmaking, an essential experience refers to a formal experience. In this case, form was a notion which constituted an idea of absoluteness and manifested through geometry.The means to liberate was fulfilled by rectification, through reconfiguration of form’s absoluteness into marks. By form reconfiguration alongside the proceedings of the painting medium, the subject matter was materialized reflectively and analogically. The painting method used in this work combined hard-edged lines and colours as in forms with gestural brushstrokes as in marks. Both form and marks rendered consequences out of each other’s dyadic relationships which existed in pairs of intersections between forms and freeflowed paintdrips and pours. These dyads could only exist as an outcome of colour boundaries as determinant variables, therefore the final result of this work demonstrated that the rectification of relations’ absolute forms instead bore dyadic principals in an autonomous painting structure which perpetually combines inclusiveness with exclusiveness.